1991
DOI: 10.1210/jcem-73-5-1129
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Tumors in Congenital Adrenal Hyperplasia: Steroid Measurements from Adrenal and Spermatic Veins

Abstract: The present study reports the case of a 25-yr-old man with congenital adrenal hyperplasia due to 21-hydroxylase deficiency in whom bilateral testicular tumors did not regress after suppressive treatment with dexamethasone. Catheterization of left testicular and adrenal veins confirmed the enzyme deficiency in the gonadal lesions. The presence of specific 11 beta-hydroxylated steroids (11 beta-hydroxyandrostenedione, 21-deoxycortisol, and 21-deoxycorticosterone) in the gonadal vein demonstrated the adrenal natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 27 publications
2
23
0
2
Order By: Relevance
“…Usually it refers to lack of regression or to recurrence after excision, even though steroidogenesis had been suppressed. Impressive cases of TAR autonomization from ACTH are the one reported by Blumberg-Tick et al (8) and especially the one reported by Clark et al (5). At 19 years of age, TAR responded to corticosteroids within one week, but 4 years later -with serum FSH at 21 mU/l and LH at 11 mU/l -TAR were unresponsive to 4 mg/day dexamethasone, even though serum 17-OH P was suppressed (5).…”
Section: Discussionmentioning
confidence: 99%
“…Usually it refers to lack of regression or to recurrence after excision, even though steroidogenesis had been suppressed. Impressive cases of TAR autonomization from ACTH are the one reported by Blumberg-Tick et al (8) and especially the one reported by Clark et al (5). At 19 years of age, TAR responded to corticosteroids within one week, but 4 years later -with serum FSH at 21 mU/l and LH at 11 mU/l -TAR were unresponsive to 4 mg/day dexamethasone, even though serum 17-OH P was suppressed (5).…”
Section: Discussionmentioning
confidence: 99%
“…5 The extra-adrenal expression of steroid 21-hydroxylase and 11␤-hydroxylase by a benign testicular Leydig cell tumor has also been reported. 6 We reported that aldosterone, synthesized in the vasculature, is in part controlled by angiotensin (Ang) II and participates in the development of vascular hypertrophy that correlates with Ang II concentration. 7,8 We performed the present study to determine whether the rat heart produces aldosterone and to investigate the effects of adrenalectomy, ACE inhibitor, and Ang II on aldosterone synthesis, aldosterone synthase activity, and the expression of aldosterone synthase gene (CYP11B2) in the heart.…”
mentioning
confidence: 99%
“…This paradoxical result could suggest poor compliance or secretion of androstenedione by the testicular tumour itself. In that case, the androstenedione level is not only the result of adrenal activity but also of tumour activity and cannot be used to assess adrenal suppression 15 ' 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In one patient (#2), the regimen of hydrocortisone 2 times a day (15 + 10 mg) was changed into dexamethasone 3 times a day (0.25 + 0.25 + 0.25 mg), to improve semen quality after oligoasthenoteratozoospermia was found and he and his wife wanted to have a child. In seven patients (#5, 6,8,12,15,16,17), the hydrocortisone regimen (3 times a day) had been changed into hydrocortisone in the morning (and afternoon) and dexamethasone in the evening. Changes in body mass index between baseline and follow-up investigation did not show a significant correlation with changes in glucocorticoid dose (Spearman rank,…”
Section: Glucocorticoid Therapy Between Baseline and Followup Investimentioning
confidence: 99%